Characteristics of Pediatric Dental Treatment Provided under General Anesthesia in Dubai, United Arab Emirates: A Retrospective Analysis - Mohammad Abdo; Manal Al Halabi; Iyad Hussein; Anas Salami; Amar H. Khamis; Mawlood Kowash (International Journal of Dentistry)
Background. Dental general anesthesia (DGA) is a widely utilized technique in pediatric dentistry and is indicated for a variety of cases such as very young children and children with special healthcare needs (SHCN). In the United Arab Emirates (UAE), there is a paucity of studies relating to this subject. Objective. To analyze the characteristics of DGA treatment in special healthcare needs and healthy children in the only postgraduate dental hospital in Dubai, UAE. Materials and Methods. A retrospective analysis was conducted on the electronic records of all Dubai Dental Hospital (DDH) pediatric patients who underwent DGA in the period between January 1st, 2016, and 29th of February 2020. Results. The study population consisted of 98 children. A total of 26 children had a medical condition and were categorized as SHCN. The most common justification for DGA was dental caries and a lack of cooperation due to young age. SHCN patients received significantly more preventive measures and significantly fewer pulp therapies than healthy patients. Conclusion. We found that the services provided under DGA for healthy pediatric patients differ from those provided to SHCN patients. Frequently missing recall appointments following DGA increased the likelihood of the need for further restorative dental treatment. These results highlight the importance of robust prevention and follow-up programs for children treated under GA.